Synthesis and catalytic applications of silver nanoparticles: a sustainable chemical approach using indigenous reducing and capping agents from Hyptis capitata. Issue 4 (12th August 2022) - Revathy, R.; Joseph, Jebin; Augustine, Cyril; Sajini, T.; Mathew, Beena
Abstract : A green protocol for the preparation of silver nanoparticles using the leaf, fruit and stem extracts of Hyptis capitata, one of the commonly found plants in the tropics. Abstract : Indigenous chemical compounds found in plants such as phenolics, alkaloids, carotenoids, xanthophylls and terpenoids are used by chemists for a variety of synthetic applications. Sustainable chemistry or green chemistry, one of the recently emerged fields of science, paved the way for such chemical compounds to act as reducing and capping agents for the syntheses of numerous metal nanoparticles. In this research paper, we suggest a green protocol for the preparation of silver nanoparticles (AgNPs) using the leaf, fruit and stem extracts of Hyptis capitata, one of the commonly found plants in the tropics. The entire shoot system of this plant is used for the synthesis of AgNPs. Using microwave irradiation, AgNPs are effectively synthesized separately with leaf, fruit and stem extracts as reducing agents and the efficacy is compared. The reaction conditions such as temperature, the amount of plant extract, and the concentration of silver nitrate, one of the precursors, are optimized to establish the most efficient methodology for the synthesis. Also, the catalytic effectiveness of such nanoparticles in removing organic dyes from aqueous systems is demonstrated. Analytical methods such as UV-visible spectroscopy, HR-TEM, EDX, SAED, XRD, DLS, measurement of zeta potential, and FT-IR analysis are used to characterize the crystalline character, chemical nature and morphology of the synthesized AgNPs. The observations confirm that the entire shoot system of Hyptis capitata is a potential biomaterial for the green synthesis of AgNPs, which can be used for the removal of dyes from aqueous systems.